Identification of novel inhibitors of the steroid sulfate carrier 'sodium-dependent organic anion transporter' SOAT (SLC10A6) by pharmacophore modelling. (15th June 2016) - Grosser, Gary; Baringhaus, Karl-Heinz; Döring, Barbara; Kramer, Werner; Petzinger, Ernst; Geyer, Joachim
Abstract: The sodium-dependent organic anion transporter SOAT specifically transports sulfated steroid hormones and is supposed to play a role in testicular steroid regulation and male fertility. The present study aimed to identify novel specific SOAT inhibitors for further in vitro and in vivo studies on SOAT function. More than 100 compounds of different molecular structures were screened for inhibition of the SOAT-mediated transport of dehydroepiandrosterone sulfate in stably transfected SOAT-HEK293 cells. Twenty-five of these with IC50 values covering four orders of magnitude were selected as training set for 3D pharmacophore modelling. The SOAT pharmacophore features were calculated by CATALYST and consist of three hydrophobic sites and two hydrogen bond acceptors. By substrate database screening, compound T 0511-1698 was predicted as a novel SOAT inhibitor with an IC50 of 15 μM. This value was confirmed by cell-based transport assays. Therefore, the developed SOAT pharmacophore model demonstrated its suitability in predicting novel SOAT inhibitors. Graphical abstract: Highlights: SOAT is a specific carrier for steroid sulfates such as DHEAS and estrone-3-sulfate in steroid responsive organs. We developed a 3D SOAT pharmacophore model based on inhibition data from ~100 compounds. The SOAT pharmacophore consists of three hydrophobic sites and two hydrogen bond acceptors. Substrate database search identified several novel SOAT inhibitors of different chemical structures. Compound T 5854015 with an IC50 of 9 µM and absent cross-inhibition of ASBT is the most promising candidate.